Life at school: An ethnographic study - Thapan, Meenakshi (New Delhi Oxford University Press, 2006)
This book explores the complex relationship between ideas, institutions, and the people in them. The author examines the Rishi Valley Schol in Andhra Pradesh, considered the hallmark of progressive education, informed by the world view of the renowned philosopher Jiddu Krishnamurti. This edition includes a new introduction that rethinks ideas in school education in light of present political and social realities. It will be of special importance to scholars of education, teachers, trainers, as also to scholars of sociology and philosophy.
Keywords: Krishnamurti, J. (Jiddu), 1895-1986; Educational anthropology--India--Andhra Pradesh